2018
DOI: 10.1111/ceo.13328
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of primary transscleral diode laser cyclophotoablation for glaucoma in Nigeria

Abstract: Transscleral diode laser cyclophotocoagulation controlled IOP in almost three quarters of eyes at 12 months with short-term preservation of vision and minimal complications. Poor follow-up in this setting highlights the need for an effective, safe and acceptable treatment where regular follow-up is less critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…However, the effect of TSCPC on IOP was unpredictable and the side effect of an atonic pupil problematic in a sunny climate. This is in contrast with other studies, showing that TSCPC is an effective and safe method as a primary procedure in the United States and Nigeria 17,18. To our knowledge, there were no African cost-analysis studies relating to TSCPC.…”
contrasting
confidence: 84%
See 1 more Smart Citation
“…However, the effect of TSCPC on IOP was unpredictable and the side effect of an atonic pupil problematic in a sunny climate. This is in contrast with other studies, showing that TSCPC is an effective and safe method as a primary procedure in the United States and Nigeria 17,18. To our knowledge, there were no African cost-analysis studies relating to TSCPC.…”
contrasting
confidence: 84%
“…This is in contrast with other studies, showing that TSCPC is an effective and safe method as a primary procedure in the United States and Nigeria. 17 , 18 To our knowledge, there were no African cost-analysis studies relating to TSCPC. Controlled cyclophotocoagulation, a modified technique of TSCPC, and the newer micropulse TSCPC offer a potential for first-line intervention; however, limited or no trials have been performed in a non-Caucasian setting.…”
mentioning
confidence: 99%
“…Although CPC has been studied in the early stages of glaucoma (Egbert et al 2001; Kramp et al 2002; Singh et al 2017b; Abdull et al 2018), its complications remain common enough to limit its use to the treatment of glaucoma refractory to conventional surgical treatments (Michelessi et al 2018; Hasan et al 2019; Paul et al 2019) (Table 3). Moreover, the inflammatory (mostly CD4 T‐cell lymphocytic infiltrates) and fibrotic histological conjunctival lesions induced by the procedure are likely to impair future filtration blebs (Tan et al 2019).…”
Section: Cw‐tscpc and Ecpmentioning
confidence: 99%
“…To our knowledge, there are no other studies of MPCPC other than those reported in this paper, although we did find the study of Abdull et al. [ 14 ], who investigated the safety and effectiveness of continuous CPC in Nigeria (Africa). In this large cohort of 201 eyes, 11 cases of mild anterior uveitis and one case of severe uveitis have been reported as complications.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, it is important to remember that Abdull et al. [ 14 ] analyzed patients treated by continuous CPC and not micropulse CPC like our patient.…”
Section: Discussionmentioning
confidence: 97%